Intervenţiile traducătorului în textul versiunii arabe din 1705 a „Divanului” lui Dimitrie Cantemir - Ioana Feodorov (Revista de Istorie și Teorie Literară)
This paper discusses the alterations, additions, and lacunae in the Arabic version of Dimitrie Cantemir’s Divan, his first printed book (Iaşi, 1698), written as he was living in Istanbul, close to the Sultan’s court, and planning to occupy the throne of Moldavia. The translator, Athanasios Dabbās, a Patriarch of the Church of Antioch and All the East, appealed to a Maronite scholar, Germānos Farāt (future Maronite Bishop of Aleppo), to revise the Arabic text, which was ready in 1705, seemingly for publishing in the Aleppo printing-house established by Dabbās that same year. The contribution of each of the two is scrutinized here, based on particular passages in the Arabic text that differ from the source-text, leading to suggestions for further research that may ascertain their specific impact on the Moldavian prince’s outstanding work.